2013 35th International Conference on Software Engineering (ICSE) 2013
DOI: 10.1109/icse.2013.6606659
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of interactive test-driven labs with WebIDE in CS0

Abstract: Abstract-WebIDE is a framework that enables instructors to develop and deliver online lab content with interactive feedback. The ability to create lock-step labs enables the instructor to guide students through learning experiences, demonstrating mastery as they proceed. Feedback is provided through automated evaluators that vary from simple regular expression evaluation to syntactic parsers to applications that compile and run programs and unit tests. This paper describes WebIDE and its use in a CS0 course th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…He found that the improvements from PSP level 0 to PSP level 2 was similar for freshmen and for graduate students. Another example is described by Janzen et al [97]. This is a study of an educational platform called WebIDE which was used to teach introductory Java and Android programming.…”
Section: Students Explicitly Desiredmentioning
confidence: 99%
“…He found that the improvements from PSP level 0 to PSP level 2 was similar for freshmen and for graduate students. Another example is described by Janzen et al [97]. This is a study of an educational platform called WebIDE which was used to teach introductory Java and Android programming.…”
Section: Students Explicitly Desiredmentioning
confidence: 99%
“…The right side of the V process involves validation and evaluation (V&E) of the system at various levels, starting from individual components and subsystems and progressing to the entire system. With the V&E activities, combat system developers [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] can ensure that each phase of development is properly verified before moving on to the next phase. It also reduces the risk of costly errors in the final system.…”
Section: Introductionmentioning
confidence: 99%
“…Neste trabalho, o foco reside no emprego de técnicas e conceitos de teste de software em atividades de aprendizagem relacionadasà resolução de problemas. Diversos trabalhos em educação em programação abordam a questão de teste de software [Utting et al 2013] e sua integração com ensino de programação, seja pela avaliação com auxílio de critérios de teste ou pela integração de atividades de teste no desenvolvimento, em variações da abordagem de desenvolvimento baseado em testes (TDD) [Edwards 2004, Janzen et al 2013, Pachulski Camara e Graciotto Silva 2016.…”
Section: Introductionunclassified